2020
DOI: 10.1186/s12889-020-8362-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of knowledge, attitude, and practices of animal and human brucellosis between nomadic pastoralists and non-pastoralists in Kenya

Abstract: Background: The seroprevalence of brucellosis among nomadic pastoralists and their livestock in arid lands is reported to be over10-fold higher than non-pastoralists farmers and their livestock in Kenya. Here, we compared the seroprevalence of nomadic pastoralists and mixed farming with their knowledge of the disease and high-risk practices associated with brucellosis infection. Methods: Across-sectional study was conducted in two counties-Kiambu County where farmers primarily practice smallholder livestock pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
(44 reference statements)
2
15
0
Order By: Relevance
“…Men too, have a greater role in treating sick livestock and thus have access to insights on livestock diseases which could explain why they are more likely to have better knowledge on brucellosis. These findings correspond to other studies which have shown a variable effect of age, gender and formal education on knowledge of brucellosis [ 44 47 ]. Here it was also found that adherence to culture was a stronger driver for engaging in behavior risking transmission, than formal education.…”
Section: Discussionsupporting
confidence: 92%
“…Men too, have a greater role in treating sick livestock and thus have access to insights on livestock diseases which could explain why they are more likely to have better knowledge on brucellosis. These findings correspond to other studies which have shown a variable effect of age, gender and formal education on knowledge of brucellosis [ 44 47 ]. Here it was also found that adherence to culture was a stronger driver for engaging in behavior risking transmission, than formal education.…”
Section: Discussionsupporting
confidence: 92%
“…Among the Maasai community, milk boiling is not favoured because it is assumed to deplete milk of nutrients; change it to a water like consistency; and make it less filling [ 12 ]. Other reasons given for preference of raw milk among pastoral communities in East Africa is that boiling makes milk less tasty [ 13 ]. As found in this study, the consumption of raw meat and fresh blood has been part and parcel of pastoral diets for many generations [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other reasons given for preference of raw milk among pastoral communities in East Africa is that boiling makes milk less tasty [ 13 ]. As found in this study, the consumption of raw meat and fresh blood has been part and parcel of pastoral diets for many generations [ 13 , 14 ]. Similarly, the use of livestock products as part of treatment processes for sick persons has also been reported in other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the infection may stay asymptomatic, and the infected animals may remain undiagnosed (1). Brucellosis is usually transmitted in animals either by contact or through ingestion of contaminated feed and water while in humans by either direct contact with infected animals or ingestion of contaminated animal products (1,(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%